Differential equations and quantum groups (European Mathematical Society, 2007)
This special volume is dedicated to the memory of Andrey A. Bolibrukh. It contains two expository articles devoted to some aspects of Bolibrukh's work, followed by ten refereed research articles. Topics cover complex linear and nonlinear differential equations and quantum groups: monodromy, Fuchsian linear systems, Riemann-Hilbert problem, differential Galois theory, differential algebraic groups, multisummability, isomonodromy, PainlevÃ© equations, Schlesinger equations, integrable systems, KZ equations, complex reflection groups, and root systems. A publication of the European Mathematical Society. Distributed within the Americas by the American Mathematical Society.